Standardisasi dan Skrining Fitokimia Ekstrak Daun Singkil (Premna corymbose) - Priamsari, Margareta Retno; Solichah, Ayu Ina; Aminah, Icha Yuliska (Jurnal Farmasi & Sains Indonesia, 2023)
Standardization is needed to obtain uniform raw materials that can guarantee the pharmacological effects of singkil plants. Phytochemical screening is the initial stage in a phytochemical research that aims to provide an overview of the class of compounds contained in the plant under study. The purpose of this study was to determine the standardization profile and class of chemical compounds in the ethanol extract of singkil leaves. This type of experimental research. Singkil leaf extraction was carried out by maceration method with 70% ethanol solvent, then followed by standardization test of singkil leaf ethanol extract. The next step is testing phytochemical compounds by identifying alkaloids, flavonoids, saponins, tannins, triterpenoids/steroids through phytochemical screening which are analyzed descriptively.The standardization results showed that the ethanol extract of singkil leaves had a dry shrinkage of 3.43%±1.28% (w/w), the extract content was soluble in water in singkil leaf powder was 20.01%±0.22% (v/w), the water soluble extract content of singkil leaf extract was 19.81 ± 0.22% (v/w), the ethanol soluble extract content of singkil leaf powder was 24.48 ± 0.24 %(v/w), ethanol soluble extract content of singkil leaf extract was 26.88 ± 1.16 %(v/w), specific gravity of singkil leaf extract was 0.91 ± 0.00 %(v/v), and ash content of singkil leaf extract. was 30.40 ± 0.00 %(w/w). The results of phytochemical screening showed that the ethanolic extract of singkil leaves contained flavonoids, tannins, saponins and triterpenoids